Representations of the 'other': a comparison between Roman descriptions of Britons, Gauls and Germans pre-AD 300 and Sir Harry Smith's portrayal of the Xhosa 1830s "“ 1850s - Van Wezel, Amy Hester (Rhodes University, Faculty of Humanities, School of Languages, 2016)
Stereotypical representations of an 'ethnically' or 'racially' different 'other' in ancient texts would seem to reappear throughout history. By comparing Roman views of Britons, Gauls and Germans, with Sir Harry Smith's views of the Xhosa, this study seeks to explore the extent to which these stereotypical images were employed and for what reasons. Through close textual analyses, the descriptions of these peoples are examined and compared, taking into consideration the different authors' context and agendas. By highlighting Caesar's views of the abilities of the 'other' and Tacitus' judgements of the moral character of the 'other', compared with Smith's view of the same, the study aims to draw out the role of the author's 'self' in complex and contradictory representations of the 'other', while arguing that various overwhelmingly negative images served to justify imperial conquest and rule. The extent to which the 'other' was perceived as remote and different from themselves, epitomised in the dichotomy between the 'barbarism' and 'civilisation', is examined, comparing a variety of Roman authors with Smith. The similar idea of 'civilising missions' are discussed, while acknowledging the differences between the policies of the Roman and British Empires toward the 'other'. The connections between how the 'other' was portrayed in relation to 'Empire' and the ways in which they were treated is also explored stressing even further the different approaches taken by Roman and British authorities to include these peoples within their Empires. While certain stereotypes are shown to have persisted from Roman times, reappearing in the writing of Sir Harry Smith, summed up in the archetypal 'barbarian', I argue that the use of these images was varied, inconsistent and reflected more the motives and personalities of the writers themselves, whofor the most part ascribed to imperial ideologies.
Keywords: Uncatalogued